A Comprehensive Study of the 14C Source Term in the 10 MW High-Temperature Gas-Cooled Reactor. Issue 5 (October 2019) - Liu, X; Peng, W; Wei, L; Lou, M; Xie, F; Cao, J; Tong, J; Li, F; Zheng, G
ABSTRACT: While assessing the environmental impact of nuclear power plants, researchers have focused their attention on radiocarbon ( 14 C) owing to its high mobility in the environment and important radiological impact on human beings. The 10 MW high-temperature gas-cooled reactor (HTR-10) is the first pebble-bed gas-cooled test reactor in China that adopted helium as primary coolant and graphite spheres containing tristructural-isotropic (TRISO) coated particles as fuel elements. A series of experiments on the 14 C source terms in HTR-10 was conducted: (1) measurement of the specific activity and distribution of typical nuclides in the irradiated graphite spheres from the core, (2) measurement of the activity concentration of 14 C in the primary coolant, and (3) measurement of the amount of 14 C discharged in the effluent from the stack. All experimental data on 14 C available for HTR-10 were summarized and analyzed using theoretical calculations. A sensitivity study on the total porosity, open porosity, and percentage of closed pores that became open after irradiating the matrix graphite was performed to illustrate their effects on the activity concentration of 14 C in the primary coolant and activity amount of 14 C in various deduction routes.